PENGARUH MODAL, DIGITAL PAYMENT, DAN LITERASI KEUANGAN TERHADAP PENGHASILAN UMKM - MERTYANI SARI DEWI; Kadek Dian Jatiwardani; Kadek Yuliastuti; Ni Luh Eka Ayu Permoni (Jurnal Pendidikan Ekonomi (JURKAMI), 2025)
As a result of the increased level of competition among business actors brought about by the rapid development of micro, small, and medium-sized enterprises, the research's central issue is that these businesses must be able to increase their level of digitalization in order to sustain and grow. A business's level of income is a gauge of its progress.  The Buleleng District's micro, small, and medium-sized businesses served as the sites of this study. 99 business actors were selected using a purposive sampling strategy and the Slovin formula.  A survey was used to collect data. Finding out how capital, digital payments, and financial literacy impact the revenue of micro, small, and medium-sized businesses in Buleleng District is the goal of this study.  The methodology used in this study is quantitative. These results show that improving the revenue of micro, small, and medium-sized businesses in Buleleng District is positively and significantly impacted by capital, digital payments, and financial literacy. The amount of revenue a business generates increases with the amount of capital used by its actors. Business actors can earn more money if they have a better level of literacy.  Additionally, the potential revenue from these commercial operations increases with the level of adoption of digital payments in transactions.